Synthesis, docking studies, in vitro cytotoxicity evaluation and DNA damage mechanism of new tyrosine-based tripeptides - Caliskan, Eray; Kaplan, Alpaslan; Sekerci, Guldeniz; Capan, Irfan; Tekin, Suat; Erkan, Sultan; Gorgulu, Ahmet O. (Wiley, 2023)
Peptides are one of the leading groups of compounds that have been the subject of a great deal of biological research and still continue to attract researchers' attention. In this study, a series of tripeptides based on tyrosine amino acids were synthesized by the triazine method. The cytotoxicity properties of all compounds against human cancer cell lines (MCF-7), ovarian (A2780), prostate (PC-3), and colon cancer cell lines (Caco-2) were determined by the 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide assay method, and % cell viability and logIC50 values of the compounds were calculated. Significant decreases in cell viability were observed in all cells (p < 0.05). The comet assay method was used to understand that the compounds that showed a significant decrease in cell viability had this effect through DNA damage. Most of the compounds exhibited cytotoxicity by DNA damage mechanism. Besides, their interactions between investigated molecule groups with PDB ID: 3VHE, 3C0R, 2ZCL, and 2HQ6 target proteins corresponding to cancer cell lines, respectively, were investigated by docking studies. Finally, molecules with high biological activity against biological receptors were determined by ADME analysis.
Keywords: ADME; cytotoxicity; DNA damage; molecular docking; peptides